Faktor-Faktor yang Memengaruhi Kadar Gula Darah pada Mahasiswi Program Studi Kebidanan Langsa Poltekkes Kemenkes Aceh - Mutiah , Cut; Munawarah, Siti (Indonesian Journal Publisher, 2025)
Background: The prevalence of hyperglycemia in adolescents is increasing. Lack of awareness for blood sugar screening causes cases of hyperglycemia to be undiagnosed. Objective: This study aims to analyze the factors influencing blood glucose levels among students of the Midwifery Study Program at Langsa Polytechnic of Health, Ministry of Health, Aceh, in 2025. Method: This study employed a cross-sectional design with a proportional sample of 51 students. The variables studied included sugar consumption patterns, physical activity, family history of diabetes, and Body Mass Index (BMI). Data were collected through questionnaires, random blood glucose level measurements, and BMI calculations. Results: The results showed that family history of diabetes (p = 0.029) and BMI (p = 0.032) had a significant relationship with blood glucose levels. In contrast, sugar consumption patterns (p = 0.347) and physical activity (p = 0.492) did not show significant associations. Conclusion: These findings indicate that genetic factors and nutritional status have a more significant impact on blood glucose levels than dietary habits and physical activity. Therefore, students with a family history of diabetes and high BMI should be more aware of their diet and lifestyle to prevent blood glucose imbalances